Factors Associated with Stunting in Toddlers Under the Service Area of Bakunase Primary Health Center in Kupang City - Kitu, Hendrika Octavia Nugraheni; Syamruth, Yendris Krisno; Purnawan, Sigit (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2023)
Introduction: Stunting or short stature is a term used for children whose height is below the average of the same sex, age, and ideally from the same racial-ethnic group (£ -2 SD). In the short term, stunting causes a slowdown of growth and development and in the long term, it has an impact on cognitive aspects and increases the risk of getting non-communicable diseases. This study aims to analyze the factors associated with the incidence of stunting in toddlers under the service area of the Bakunase Primary Health Center, Kupang City.Methods : This research is an analytical survey, with a case-control design. A total 136 toddlers which were divided into 68 case groups and 68 control groups were recruited. The recruited participants were selected using a simple random sampling method. The mother's knowledge, attitude, parenting style, living environment and the incidence of diarrhea were investigated. Data was collected using a questionnaire. The chi-square statistical test was used and Odd Ratios were calculated.Results: The results showed that there was a relationship between mother's knowledge (p-value = 0.000, OR = 6.667), mother's attitude (p-value = 0.000, OR = 5.808), mother's parenting style (p-value = 0.000, OR = 5.093), living environment (p-value = 0.000, OR = 7.538), and the incidence of diarrhea (p-value = 0.002, OR = .3.175) with the incidence of stunting in toddlers the Bakunase Primary Health Center service area, Kupang City.Conclusion: It was concluded that there was a relationship between mother's knowledge, mother's attitude, mother's upbringing, living environment and the incidence of diarrhea with the incidence of stunting in toddlers. Therefore, health promotion and cross-sector cooperation are needed to overcome the problem of stunting.